Othello, the Moor of Venice - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
Othello is one of the most powerful tragedies of William Shakespeare. Othello is a Moorish general who falls in love with Desdemona, the daughter of a powerful senator of Venice. The play is about their love and Othello s mistrust and jealousy, which ultimately leads to a murder. This short narrative version of the play has been suitably adapted to help introduce the play to young readers
Keywords: Adaptations Juvenile literature